CADMIUM CHLORIDE INDUCED CHANGES IN PROTEIN MOLECULES OF THE FRESHWATER FISH CIRRHINUS MRIGALA (HAMILTON) - K, Veeraiah; K, Jaya Raju; P, Padmavathi; A, Samyuktha Rani; Ch, Vivek (Innovare Journal of Life Sciences, 2013)
Abstract Â Â Â Â Â Â Â Â Â Â Â Â Â Â Â Â Â Â Â Â Â The fresh water fish Cirrhinus mrigala (Hamilton) was exposed to the heavy metal Cadmium chloride for 24, 48, 72, and 96 h, and the consequential LC50 values were calculated using Finney's probit analysis. The LC50 values obtained for 24, 48, 72, and 96 h were 317.5, 316.5, 316.0 and 315.5 respectively. Later the fish were exposed to 96 h acute lethal and sub-lethal concentrations and the changes in protein subunits were analyzed in the tissue of the vital organs such as brain, liver, muscle, gill and kidney using SDS-PAGE electrophoresis. The results revealed that among the protein molecules some became faded when compared to control fish protein molecules, whereas some protein bands disappeared. The analysis was made with the help of standard protein marker. The changes are more pronounced in the tissue of liver and muscle, which may be due to the involvement of liver in the detoxification mechanism. Whereas in case of muscle the changes in the protein banding pattern may be due to the consumption of energy through erratic movement caused due to the toxicant stress. It was also observed that the changes in kidney protein molecules is also more and this may beÂ due to the accumulation of cadmium chloride in kidney tissue. The results obtained were discussed at length with the available literature. Â Key words: Cadmium chloride, Cirrhinus mrigala, Protein molecules, Liver, LC50 and Â Â Â Â Â Â Â SDS-PAGE.